Chapter 28 Measures of Ageism in the Labour Market in International Social Studies (2018)
With population ageing, ageism towards older workers has been brought to the attention of researchers and policymakers. This chapter provides an overview and evaluation of existing indicators measuring ageism in the labour market in large-scale international surveys. We present results from an international descriptive comparison of 18 self-reported indicators from seven surveys. These indicators measure attitudes, perceptions, values and experiences with regard to older adults’ labour market participation, and are grouped into the following five aspects of ageism in the labour market: recruitment/retention; performance; training; interaction with older colleagues; and structural ageism. A preliminary taxonomy of measures is developed based on the findings, and recommendations for further research are provided.